Greenhouse Gas Emissions and Human Development: Implications for Climate Change Impacts in Africa - Praise, Ubi-Abai Itoro; Mbobo, Enobong Udemeabasi (International Journal of Climate Research, 2020)
This study examined the effects of greenhouse gas (GHG) emissions on human development, particularly focusing on its impacts on the human development in Africa. The paper first discussed the trends in global GHG emissions and human development, and subsequently adopted the ARDL estimation technique to examine the effects of GHG emissions on human development in Africa from two perspectives. This involved examining and comparing the effects of GHG emissions from African countries and that from the rest of the world (ROW) on the human development in the region at two periods in time. Results showed that GHG emissions from Africa and from the ROW are increasing. Moreover, both have the same effects on human development in Africa in two periods in time. These effects were positive and significant in the short run, and negative and significant in the long run. The former implies that as GHG emissions increase in the short run, human development improves. Conversely, the latter means that as GHG emissions increased in the long run, human development retards. The comparative analysis showed that, in the short run, GHG-emitting activities from the ROW have benefited African countries much more than what they can produce for themselves. However, GHG-emitting activities from the ROW emit GHGs larger than that emitted in Africa in the long run which causes climate change with undesirable consequences that undermine human development in Africa. Finally, various strategic mitigation procedures and adaptive measures were recommended.